1 - Introduction: Ideologies of Youth - Van Dijk, Rijk; De Bruijn, Mirjam; Cardoso, Carlos; Butter, Inge (Africa Development, 2021)
In a number of countries in Africa, such as Uganda and Kenya, national publics have been discussing whether citizens of age 50 or even 60 should be regarded as ‘youth’. Under the current dispensation of do- nor funding, relief programmes and international aid, these discussions have made the ‘youth’ the major beneficiary of what these policies offer and imply. There is a general feeling, however, that these policies should target all age groups in their youth-oriented programmes. If the donor- ideology prescribes youthfulness for societal and developmental rel- evance, it will then dictate practice. This is just one example of what this special issue will address in an attempt to explore what we see as an emerging development in Africa and beyond: the rise of youth as an ideology. Whereas Africa has witnessed the rise of a fast-growing study of youth as a phenomenon and as a concept, the aspect of youth as ideology has, so far, not been elaborated on.